INFLATION IN CENTRAL SULAWESI: MONETARY PHENOMENON OR FISCAL PHENOMENON? - Anam, Haerul; Rahman, Failur; Mujirin (Tadulako Social Science and Humaniora Journal, 2020)
The study aims to analyse inflation inCentral Sulawesi province by proving two inflation theories as inflation as a monetary phenomenon or fiscal phenomenon and in response to fiscal policy conducted by the central government through a fiscal variable in suppressing the inflation rate in Central Sulawesiprovince, Indonesia. The approach is to look at comparative levels of significance from fiscal variables and monetary variables in influencing inflation through non-nestedtests.The results obtained from estimates made to fiscal variables and monetary variables indicate that the monetary variable has a better and more significant influence on the consumer price Index (CPI) variable than the fiscal variable, so it can be concluded that inflation occurring in central Sulawesi province is a monetary phenomenon.